2020
DOI: 10.1016/j.sjbs.2019.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Dual-curing resin cement with colour indicator for adhesively cemented restorations to dental tissues: Change of colour by curing and some physical properties

Abstract: The study was aimed to investigate a color indicator containing dual curing resin composite luting cement and to plot the color change to the time of solidification of the cement. In addition some physical properties were studied. Specimens were made of a dual-cure resin cement (Maxcem Elite™ Chroma, Kerr, Orange, CA, USA) and polymerized by autopolymerization only, or with light initiated polymerization. A spectrophotometer was used to quantify the color change of the cement as plotted with the curing time. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…When the different modes of activation were tested, in group CA, the DC of the cements used in this research were shown to be lower than those in group L, showing the need for exposure to light. In fact, the result obtained in this research corroborated the findings of various studies (Alovisi et al, 2018;Arrais et al, 2008;Chen et al, 2016;El-Mowafy et al,1999;Inokoshi et al, 2021;Jang et al, 2017;Kim et al, 2017;Majumder et al, 2019;Niemi et al, 2020;Shim et al, 2017) and demonstrated the dependence on light activation of dual cements, and this is probably related to the differences in the proportion between the initiator and accelerator. The type of amine used as accelerator may also have influenced polymerization (Caughman et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…When the different modes of activation were tested, in group CA, the DC of the cements used in this research were shown to be lower than those in group L, showing the need for exposure to light. In fact, the result obtained in this research corroborated the findings of various studies (Alovisi et al, 2018;Arrais et al, 2008;Chen et al, 2016;El-Mowafy et al,1999;Inokoshi et al, 2021;Jang et al, 2017;Kim et al, 2017;Majumder et al, 2019;Niemi et al, 2020;Shim et al, 2017) and demonstrated the dependence on light activation of dual cements, and this is probably related to the differences in the proportion between the initiator and accelerator. The type of amine used as accelerator may also have influenced polymerization (Caughman et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…The clinical significance of this study is in agreement with the studies of various authors and allow us to affirm that chemical polymerization is insufficient to enable conventional dual resin cements to attain complete polymerization, resulting in lower DC (Alovisi et al, 2018;Arrais et al, 2008;Chen et al, 2016;El-Mowafy et al, 1999;Inokoshi et al, 2021;Jang et al, 2017;Kim et al, 2017;Majumder et al, 2019;Martins et al, 2019;Niemi et al, 2020;Shim et al, 2017) and CS (Chen et al, 2016;Jang et al, 2017;Kim et al, 2017;Shim et al, 2017). Special clinical steps must be taken, such as increasing the time of polymerization to compensate the attenuated intensity of light during cementation of resin and ceramic restorations (Almeida et al, 2018;Hardy et al, 2018;Jang et al, 2017;Majumder et al, 2019;Shim et al, 2017;Shim et al, 2018;Turp et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Dual cure resin cement has improved mechanical qualities, including flexural strength and hardness, in addition to the advantage of favoring better polymerization to MZ. [ 9 ] This has been proven by Magne et al . [ 4 ] with different luting types of cement and zirconia primers; zirconia exhibits improved bond strength.…”
Section: Discussionmentioning
confidence: 73%
“…Resin cements are classified according to their method of activation into chemically cured, lightcured and dual-cured. In chemically-cured resin cements, color instability and lack of control over the working time make clinicians prefer to use either light-cured or dual-cured resin cements in luting of restorations [12].…”
Section: Introductionmentioning
confidence: 99%